2022
DOI: 10.3390/foods11111581
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antihypertensive, Hypoglycaemic and Nootropic Activity of a Polyphenolic Extract from the Halophyte Ice Plant (Mesembryanthemum crystallinum)

Abstract: This study aims to determine the potential antioxidant, antihypertensive, hypoglycaemic and nootropic activity of a purified polyphenolic extract from the halophyte ice plant (Mesembryanthemum crystallinum). The ice plant extract showed good antioxidant activity measured by DPPH, ORAC, TEAC, FRAP and ferrous ion chelating activity. Moreover, the extract showed potent ACE, DPP-IV and PEP-inhibitory activity (90.5%, 98.6 % and 73.1%, respectively, at a final concentration of 1 mg/mL). The extract was fractionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 70 publications
0
25
1
Order By: Relevance
“…M. crystallinum , a moderate halophyte also called the ice plant, is recently deserving of great interest due to its multiple applications, not only as an edible plant but also because of its nutraceutical properties and as a physiological model for the transition between C3 and CAM metabolisms [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…M. crystallinum , a moderate halophyte also called the ice plant, is recently deserving of great interest due to its multiple applications, not only as an edible plant but also because of its nutraceutical properties and as a physiological model for the transition between C3 and CAM metabolisms [ 11 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of toxic metals in plant tissues is important not only to establish the possible application of this plant in phytoremediation [ 15 , 16 ], but also to establish whether its cultivation in polluted soils could be safe; particularly considering that it has pharmaceutical applications [ 13 , 14 ]. Our results demonstrate that the plant accumulated metals mainly in roots, with a strong limitation of translocation to the shoot.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its efficacy in the treatment of diabetes, hypertension, and obesity, since ice plant extract prevents lipogenesis and increases lipolysis, ice plant research in Korea is still insufficient [ 3 ]. The ice plant exhibits a wide range of activities, including antioxidant properties; radical scavenging activity [ 4 , 5 ]; and antihypertensive, hypoglycemic, hyperglycemic, nootropic [ 6 ], and memory-improving activity [ 7 ]. It has been reported that ice plant ( Mesembryanthemum crystallinum ) extract ameliorates hyperglycemia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%